Improvement of English Speaking Skills in Madrasah Aliyah in Wajo District - Satriani, Satriani; Alias, Hamzah; Hasbi, Muhammad (Education and Talent Development Center of Indonesia, 2022)
The future younger generation of the Indonesian nation must have adequate foreign language skills, especially English. This foreign language is needed to support the main knowledge he has, such as knowledge of religion, politics, law, economics, literature, mathematics, biology, chemistry, engineering, medicine, and others. Therefore, at this time, it is unavoidable that global competition and competitiveness have prompted various groups of people to need strategic tips for expanding globally. Therefore, community service is carried out by FTK IAI lecturer As'Adiyah Wajo to provide training and guidance to MA in Wajo Regency.